The Integration of Character Education in Social Sciences Learning Through Study of Macapat Song - Ari Aromandani (Universitas Negeri Malang, 2015)
Pengintegrasian Pendidikan Karakter dalam Pembelajaran IPS Melalui Kajian Tembang Macapat Abstract: The research to describe how the implementation of character education which integrated by teaching process of IPS by local culture. The focus of this research are: (1) the form of the integration of character education in social studies learning through song Macapat study, (2) the value of the characters contained in the text of the song Macapat, (3) the implementation of the value of the character in the song Macapat daily life of students. This study uses a qualitative descriptive case study. Techniques used to collect the data: (1) interviews, (2) observation, (3) documentation. The data have been obtained and tested again using a triangulation technique that consists of triangulation methods, sources and theories as well as member check (checking membership).The result of these researches: (1) the integration of character education in learning of social studies subject by analyzing of Macapat song done in three time meetings and three steps, these was planning, implementing and evaluating. Every step was include character value religious, responsibility and honest, (2) Macapat song had so many character value which could be internalized in the development of student education. (3) the implementation of character values of Macapat song in student daily life had not been achieved the maximum result yet. Key Words: character education, learning of IPS, macapat song   Abstrak: Penelitian ini bertujuan mendeskripsikan penerapan pendidikan karakter yang diintegrasikan dalam proses belajar mengajar (PBM) IPS melalui budaya lokal. Fokus penelitian ini adalah: (1) bentuk pengintegrasian pendidikan karakter dalam pembelajaran IPS melalui kajian tembang Macapat, (2) nilai karakter yang terkandung di dalam teks tembang Macapat, (3) implementasi nilai karakter tembang Macapat dalam kehidupan sehari-hari siswa. Penelitian ini menggunakan metode deskriptif kualitatif dengan studi kasus. Teknik pengumpulkan datanya adalah: (1) wawancara, (2) observasi, (3) dokumentasi. Data yang telah diperoleh diuji lagi dengan menggunakan teknik triangulasi yang terdiri dari triangulasi metode, sumber, dan teori serta member check (pengecekan keanggotaan). Hasil penelitian adalah sebagai berikut. (1) Pengintegrasian pendidikan karakter dalam pembelajaran IPS melalui kajian tembang Macapat dilakukan dalam tiga kali pertemuan serta tiga tahap yaitu perencanaan, pelaksanaan dan evaluasi. (2) Tembang Macapat mengandung banyak nilai karakter yang dapat diinternalisasikan dalam mengembangkan pendidikan karakter siswa. (3) Implementasi nilai karakter tembang Macapat dalam kehidupan sehari-hari siswa belum memberikan hasil yang maksimal. Kata kunci: pendidikan karakter, pembelajaran IPS, tembang macapat